Cardiovascular Disease and Thrombosis in HIV Infection. Issue 2 (1st December 2022) - Perkins, Megan V.; Joseph, Sarah B.; Dittmer, Dirk P.; Mackman, Nigel
Abstract : HIV infection has transitioned from an acute, fatal disease to a chronic one managed by antiretroviral therapy. Thus, the aging population of people living with HIV (PLWH) continues to expand. HIV infection results in a dysregulated immune system, wherein CD4 + T cells are depleted, particularly in the gastrointestinal tract, disrupting the gut epithelial barrier. Long-term HIV infection is associated with chronic inflammation through potentially direct mechanisms caused by viral replication or exposure to viral proteins and indirect mechanisms resulting from increased translocation of microbial products from the intestine or exposure to antiretroviral therapy. Chronic inflammation (as marked by IL [interleukin]-6 and CRP [C-reactive protein]) in PLWH promotes endothelial cell dysfunction and atherosclerosis. PLWH show significantly increased rates of cardiovascular disease, such as myocardial infarction (risk ratio, 1.79 [95% CI, 1.54–2.08]) and stroke (risk ratio, 2.56 [95% CI, 1.43–4.61]). In addition, PLWH have increased levels of the coagulation biomarker D-dimer and have a two to ten-fold increased risk of venous thromboembolism compared with the general population. Several small clinical trials analyzed the effect of different antithrombotic agents on platelet activation, coagulation, inflammation, and immune cell activation. Although some markers for coagulation were reduced, most agents failed to reduce inflammatory markers in PLWH. More studies are needed to understand the underlying mechanisms driving inflammation in PLWH to create better therapies for lowering chronic inflammation in PLWH. Such therapies can potentially reduce atherosclerosis, cardiovascular disease, and thrombosis rates in PLWH and thus overall mortality in this population.